Autologous stem cell transplantation in atypical mycosis fungoides with central nervous system involvement: follow-up. (October 2021) - Sirsikar, Prachitee; Doerschne, Mirjam; Pekar-Lukacs, Agnes; Messerli-Odermatt, Olivia; Dommann-Scherrer, Corina; Rütti, Markus; Müller, Antonia M; Nair, Gayathri; Kamarachev, Jivko; Kerl, Katrin; Beer, Markus; Messerli, Markus; et al.
Abstract : Mycosis fungoides (MF) is a presentation of primary cutaneous T-cell lymphoma with adverse prognosis for patients with advanced stages of the disease. Refractory disease and advanced-stage disease require systemic therapy. We reported a rare case of an atypical predominantly CD8+ folliculotropic MF, a subtype of MF with poorer prognosis, in a 59-year-old woman. She was initially diagnosed with MF restricted to the skin, of T3N0M0B0/stage IIB according to the current World Health Organization–European Organisation for Research and Treatment of Cancer classification. First-line treatment with local percutaneous radiotherapy in combination with systemic interferon alfa-2a resulted in complete remission. However, 21 months later the disease progressed to T3N0M1B0/stage IVB with development of cerebral manifestation and thus very poor prognosis. Allogeneic stem cell transplantation (SCT) was not a therapeutic option due to the lack of a suitable donor. We initiated methotrexate and cytarabine chemotherapy, followed by high-dose chemotherapy with thiotepa and carmustine with autologous SCT. Despite rapid response and complete remission of the cerebral lesions, disease recurrence of the skin occurred soon after. Readministration of interferon alfa-2a as a maintenance treatment after the salvage autologous SCT resulted in a complete remission during a follow-up period of 32.5 months after autologous SCT. After that, the disease relapsed with simultaneous skin and cerebral lesions. Despite immediate intrathecal and subsequently intravenous administration of high-dose methotrexate and cytarabin, we observed further progressed and the patient deceased 3.5 months after this second fulminant recurrence and in total 36 months after autologous SCT transplantation.